Best Answer

So -3x - 6 = x - 4, ie -2 = 4x so x = -½ and y = -4½

Q: What is the answer to y equals -3x-6 y equals x-4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

y=x+2if y=66=x+26-2=x4=xso x=4

(x + y)2 = x2 + 2xy + y2 So x2 + y2 = (x + y)2 - 2xy = a2 - 2b Then (x2 + y2)2 = x4 + 2x2y2 + y4 So x4 + y4 = (x2 + y2)2 - 2x2y2 = (a2 - 2b)2 - 2b2 = a4 - 4a2b + 4b2 - 2b2 = a4 - 4a2b + 2b2

18 = 3x6 = x

3x6, 9x2, 18x1,

To solve the equation n + 3x6 = 30, first calculate 3x6, which equals 18. Then subtract 18 from both sides of the equation to isolate n. Thus, n = 30 - 18, which simplifies to n = 12.

Related questions

If the question is, Is y = x4 an exponential function ? then the answer is no.An exponential function is one where the variable appears as an exponent.So, y = 4x is an exponential function.

y=x+2if y=66=x+26-2=x4=xso x=4

(x2 + y2)(x + y)(x - y) = x4 - y4.

x = 8y = 6(5x8) + (3x6) = 58(5x8) - (3x6) = 22

(x + y)2 = x2 + 2xy + y2 So x2 + y2 = (x + y)2 - 2xy = a2 - 2b Then (x2 + y2)2 = x4 + 2x2y2 + y4 So x4 + y4 = (x2 + y2)2 - 2x2y2 = (a2 - 2b)2 - 2b2 = a4 - 4a2b + 4b2 - 2b2 = a4 - 4a2b + 2b2

18 = 3x6 = x

3x6, 9x2, 18x1,

To solve the equation n + 3x6 = 30, first calculate 3x6, which equals 18. Then subtract 18 from both sides of the equation to isolate n. Thus, n = 30 - 18, which simplifies to n = 12.

28 is.

7

yes

Not necessarily.